Some new perspectives on the Soweto uprising: H. M. L. Lentsoane’s poem “Black Wednesday” (“Laboraro le lesoleso”) - Antjie Krog (Tydskrif vir Letterkunde, 2022)
The epic poem about the Soweto uprising, “Laboraro le lesoleso”, written in Sepedi (Northern Sotho) by H. M. L. Lentsoane has only recently been translated into English by Biki Lepota as “Black Wednesday” and published in the anthology Stitching a whirlwind (2018). In this article I suggest that, by discarding English, some crucial shifts from the bulk of protest poetry written in English must have taken place. Lentsoane wants to speak directly to fellow mother tongue speakers and not a national or broader African or international ear. It becomes clear that, by deploying various strategies based in orality, the poet manages to contribute new material and new approaches to creative texts of black protest during the apartheid years, e.g., a release from specific apartheid content about their oppression that every indigenous speaker had common knowledge of; an adherence to orality in terms of presentation, vocabulary, and form; and a linkage with the ancestors and a release from trying to reach the conscience of whites. This manifests through the poem’s particular perspective and emphasis as narrative, as telling, combined with vivid visceral poetic imagery of the event. The poem evocatively captures the unfolding of incidents while at the same time shifting the focus to an ancestral demand to stand up for righteousness in a universal field of justice.